Aristotle’s Distributive Justice as the Basis for Evaluating Criteria for Low-Income Individuals Receiving Legal Aid - Indra Purwanto (Journal of Human Interaction and Social Studies, 2026)
This study examines the philosophical and juridical foundations of legal aid eligibility criteria for low income individuals in Indonesia through the perspective of Aristotle’s distributive justice. The research employs a non empirical normative legal method using statutory, conceptual, and philosophical approaches. Primary legal materials include the Constitution of the Republic of Indonesia of 1945, Law Number 16 of 2011 concerning Legal Aid, and Government Regulation Number 42 of 2013. The analysis reveals that the existing legal aid framework primarily relies on administrative indicators of poverty, particularly certificates of indigence and social assistance documentation. While these mechanisms provide procedural certainty, they do not adequately capture actual legal vulnerability, social exclusion, and barriers to accessing justice. Aristotle’s distributive justice demonstrates that the allocation of legal aid should be based on proportional need rather than formal administrative status alone. The study proposes a reconstructed eligibility model incorporating economic capacity, social vulnerability, legal access barriers, legal literacy, and structural disadvantage. Such a framework strengthens substantive justice, improves the accuracy of legal aid distribution, and enhances the realization of equal access to justice within Indonesia’s constitutional legal order.